Analisis Karakteristik Udara Pendingin Terhadap Kinerja Air Conditioner (AC) - Aqilvin Berliansyah; Arwizet Karudin; Refdinal Refdinal; Remon Lapisa (Jurnal Vokasi Mekanika (VoMek), 2025)
A stable room temperature is essential for comfort. This study tests the performance of split wall air conditioners with R-22 refrigerant and evaluates how to improve their efficiency through the influence of cooling air temperature. The experiment was carried out by varying the air temperature and cooling load using a heater. Data is taken every 15 minutes for 2 hours using a digital thermometer. The results showed that the maximum coefficient of performance (COP) value reached 8 indoors and 7.2 outdoors. Meanwhile, the maximum energy efficiency ratio (EER) value was recorded at 4.2 indoors and 3.7 outdoors. The stability of COP and EER values indicates that the Split Air Conditioner can operate efficiently despite variations in air temperature and cooling load. Cooler cooling air proved to be crucial in improving system efficiency. Conversely, higher refrigerant loads tend to decrease efficiency. However, this drop can be minimized by keeping the cooling air temperature low. The selection of the appropriate refrigerant, such as R-22, also plays an important role in supporting optimal performance. The combination of cooler cooling air and the right refrigerant allows the split air conditioner to operate with high efficiency. This research provides an important basis for the development of energy-efficient and efficient cooling systems. Optimizing the temperature of the cooling air is one of the main keys in improving the efficiency of the cooling system. With the right approach, split air conditioners can be used more effectively to create thermal comfort while saving energy.